Epigenome signatures landscaped by histone H3K9me3 are associated with the synaptic dysfunction in Alzheimer's disease. Issue 6 (17th May 2020) - Lee, Min Young; Lee, Junghee; Hyeon, Seung Jae; Cho, Hyesun; Hwang, Yu Jin; Shin, Jong‐Yeon; McKee, Ann C.; Kowall, Neil W.; Kim, Jong‐Il; Stein, Thor D.; Hwang, Daehee; Ryu, Hoon
Abstract: The pathogenesis of Alzheimer's disease (AD) and the commonest cause of dementia in the elderly remain incompletely understood. Recently, epigenetic modifications have been shown to play a potential role in neurodegeneration, but the specific involvement of epigenetic signatures landscaped by heterochromatin has not been studied in AD. Herein, we discovered that H3K9me3‐mediated heterochromatin condensation is elevated in the cortex of sporadic AD postmortem brains. In order to identify which epigenomes are modulated by heterochromatin, we performed H3K9me3‐chromatin immunoprecipitation (ChIP)‐sequencing and mRNA‐sequencing on postmortem brains from normal subjects and AD patients. The integrated analyses of genome‐wide ChIP‐ and mRNA‐sequencing data identified epigenomes that were highly occupied by H3K9me3 and inversely correlated with their mRNA expression levels in AD. Biological network analysis further revealed H3K9me3‐landscaped epigenomes to be mainly involved in synaptic transmission, neuronal differentiation, and cell motility. Together, our data show that the abnormal heterochromatin remodeling by H3K9me3 leads to down‐regulation of synaptic function‐related genes, suggesting that the epigenetic alteration by H3K9me3 is associated with the synaptic pathology of sporadic AD. Abstract : Histone H3K9me3 is densely stained in nuclear foci where heterochromatins are spatially localized in neurons of AD temporal cortex. H3k9me3‐heterochromatin‐landscaped epigenomes are closely associated with the synaptic dysfunction in AD. Together, the epigenetically disrupted biological pathways could serve as novel biomarkers in AD.